Normative bedrock response-dependence, rationality, and reasons - Gert, Joshua (Oxford : Oxford University Press, 2012)
Gert offers an account of normative facts and properties, those which have implications for how we ought to behave. He argues that our ability to think and talk about normative notions such as reasons and benefits is dependent on how we respond to the world around us, including how we respond to the actions of other people.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Normativity (Ethics)